Gestiona la procrastinación y dirige tu día (Assemble You, 2022)
Welcome to Audio Learning by Assemble You. In a survey of more than 2,000 people, 88% admitted to procrastinating for at least an hour every day, and nearly 60% admitted to procrastinating for more than two hours a day. If you want to make the most of your time so that you can be more productive and more successful than your peers, listen to the 5 tricks that we provide you in this 10-minute recording. Learning objectives Learn 5 tricks to stop procrastination, and thus boost your productivity Learn to take control of your time and get more out of your day.